CAN AUDIT COMMITTEE MODERATE FRAUD HEXAGON MODELS IN DETECT FRAUDULENT FINANCIAL REPORTS: AN EMPIRICAL STUDY OF PROPERTY AND REAL ESTATE SECTOR COMPANIES IN INDONESIA - Hakim, Mohamad Zulman; Imam Hidayat; Januar Eky Pambudi; Aura Putri Rahmawati; Hesti Febriatul Lubnaningtyas; Eldi Efriadi (ZILLZELL MEDIA PRIMA, 2024)
This study seeks to provide empirical evidence of the impact of the Fraud Hexagon on fraudulent reports, with the Audit Committee serving as a moderating variable. The research focuses on companies in the property and real estate sectors listed on the Indonesia Stock Exchange 2020-2022 period. The object of this study is to examine the relationship between the elements of the fraud hexagon and financial statement fraud while considering the influence of the audit committee. This study employs regression analysis with MRA (modified regression analysis) for the purpose of data analysis. The findings of this study indicate that financial target, financial stability, external pressure, CEO education, nature of industry, CEO picture, audit opinion, and effective monitoring do not exert any influence on the likelihood of dishonest financial reporting. Simultaneously, alterations in leadership and political affiliations have an influence on deceitful financial statements within the property and real estate industries. Meanwhile, the audit committee can oversee the inadequate supervision of fraudulent financial reporting.